Reliable Bone Source in Forensic Investigations to Determine the Age by X-Ray Radiography of Pakistani Population (Medical Forum Monthly, 2020)
Objective: To know the reliable bone source in forensic investigations to determine the age by x-ray radiography of Pakistani population.Study Design: Cross sectional studyPlace and Duration of Study: This study was conducted at the Forensic Medicine Department, Government Khawaja Muhammad Safdar Medical College, Sialkot and UHS, Lahore from July 2019 to June 2020.Materials and Methods: For age assessment at hand-wrist joint 60 subjects aged between 5-19 years and posteroanterior radiographs of chest were examined to determine age at sternal end of the clavicle of 62 subjects aged between 17 to 27 years were selected for this cross-section study. Chronological and skeletal age of each participant was observed.Results: The age range from 5-19 years with mean chronological age for male was 9.96±3.04 while mean skeletal age for male subjects was found 9.30±3.21. Mean chronological age for female subjects was 9.13±2.68 while mean skeletal age for female subjects was 8.65±3.06. Results of G&P method were found to be statistically significant for both males and females. The mean with interquartile range for stages 2-5 by gender. Stage 2 was first found in both genders at the age of 17.Conclusion: For age assessment at hand and wrist joint Greulich & Pyle method proved to be reliable for use is Pakistani population. When compared to other populations, Pakistani population followed a delayed and narrow time frame for development of medial epiphysis of clavicle. At stage 5 of ossification minimum age estimated was 25 years for both genders.